2008
DOI: 10.1161/strokeaha.107.500124
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Background Blood–Brain Barrier Integrity Between Lacunar and Cortical Ischemic Stroke Subtypes

Abstract: Background and Purpose-Lacunar stroke is associated with endothelial dysfunction and histologically with intrinsic cerebral microvascular disease of unknown cause. Endothelial dysfunction could impair blood-brain barrier integrity.We assessed background blood-brain barrier leakage in patients with lacunar ischemic stroke compared with cortical stroke controls. Methods-We recruited patients with lacunar or mild cortical ischemic stroke and assessed generalized cerebral blood-brain barrier leak with MRI and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 27 publications
(30 reference statements)
6
73
0
1
Order By: Relevance
“…44 More recently, contrast-enhanced MRI has been used to study BBB permeability, documenting an increased permeability in the white matter of patients with lacunar stroke compared with patients with cortical stroke. 45 Topakian et al 46 found increased BBB permeability in normal appearing white matter in patients affected by SVD compared with controls, and white-matter lesion severity was an independent predictor of these permeability-related signal changes.…”
Section: Evidence Of Endothelial Dysfunction/ Damage In Small Vessel mentioning
confidence: 99%
“…44 More recently, contrast-enhanced MRI has been used to study BBB permeability, documenting an increased permeability in the white matter of patients with lacunar stroke compared with patients with cortical stroke. 45 Topakian et al 46 found increased BBB permeability in normal appearing white matter in patients affected by SVD compared with controls, and white-matter lesion severity was an independent predictor of these permeability-related signal changes.…”
Section: Evidence Of Endothelial Dysfunction/ Damage In Small Vessel mentioning
confidence: 99%
“…The magnetic resonance imaging mean diffusivity discriminates WMH from normal-appearing WM even within the mild range of WMH severity, suggesting that BBB leak is an early predictor of WM damage. 79,80 There are accumulating lines of evidence in support of a pivotal role of the BBB leakage in SVD stroke [81][82][83] and in VCI. 84 Therefore, endothelial damage and subsequent BBB breakdown seem to be pivotal factors contributing to the pathogenesis of SVD.…”
Section: Important Roles Of Cell Components Of Bbb In Svdmentioning
confidence: 99%
“…Средний коэффициент диффузии при магнитно-резонансной томографии позволяет отли-чить ГБВГМ от нормального БВГМ даже при умерен-ной тяжести ГБВГМ, подтверждая, что повышение проницаемости ГЭБ является ранним предиктором повреждения БВГМ [79,80]. Растет число доказа-тельств в поддержку ключевой роли разрушения ГЭБ при инсульте на фоне БМЦС [81][82][83] и при СКН [84]. Таким образом, повреждение эндотелия и последую-щее разрушение ГЭБ являются основополагающими факторами в патогенезе БМЦС.…”
Section: важная роль клеточных компонентов гэб при бмцсunclassified
“…1 However, it is unclear whether leukoaraiosis has a predominantly ischemic etiology due to either chronic ischemia 22,23 or incomplete episodic infarction or whether it represents a primary microangiopathy that directly causes both leukoaraiosis and the associated physiological changes. 5,24 Although both hypotheses could explain the clinical associations, the former hypothesis is supported by studies showing a relationship between the anatomic distribution of leukoaraiosis and lower cerebral blood flow 22 or cerebrovascular reactivity, 25 whereas …”
mentioning
confidence: 98%